Panorama of photovoltaic energy in poultry in Paraná (Research, Society and Development, 2022)
Brazil stands out before other countries for having a gigantic area for food production. Paraná is the state that stands out among the nation's states with its gross production value (VBP), which in these values are the agricultural and livestock productions such as poultry farming. Moreover, Paraná stands out for having a high solar irradiation, which leads rural entrepreneurs to seek the use of renewable energies as electric energy, especially photovoltaic energy. With that, the present study refers to a qualitative systematic review, whose objective was to conduct an analysis of the scientific production on the panorama of solar photovoltaic energy in poultry farming in the state of Paraná, in the period from 2012 to 2021. The bibliographical search was carried out in the databases: Scopus and Scielo including others described on the theme, searching for information from government agencies responsible for production indicators, growth and development. This review showed that the State of Paraná has a great potential for photovoltaic solar energy generation, by the levels of solar radiation which is inserted and also for having the largest poultry herd in Brazil.